Mitochondrial-related microRNAs and their roles in cellular senescence - Luo, Ling; An, Xingna; Xiao, Yinghui; Sun, Xiguang; Li, Sijie; Wang, Yingzhao; Sun, Weixia; Yu, Dehai (Frontiers in Physiology, 2024)
Aging is a natural aspect of mammalian life. Although cellular mortality is inevitable, various diseases can hasten the aging process, resulting in abnormal or premature senescence. As cells age, they experience distinctive morphological and biochemical shifts, compromising their functions. Research has illuminated that cellular senescence coincides with significant alterations in the microRNA (miRNA) expression profile. Notably, a subset of aging-associated miRNAs, originally encoded by nuclear DNA, relocate to mitochondria, manifesting a mitochondria-specific presence. Additionally, mitochondria themselves house miRNAs encoded by mitochondrial DNA (mtDNA). These mitochondria-residing miRNAs, collectively referred to as mitochondrial miRNAs (mitomiRs), have been shown to influence mtDNA transcription and protein synthesis, thereby impacting mitochondrial functionality and cellular behavior. Recent studies suggest that mitomiRs serve as critical sensors for cellular senescence, exerting control over mitochondrial homeostasis and influencing metabolic reprogramming, redox equilibrium, apoptosis, mitophagy, and calcium homeostasis-all processes intimately connected to senescence. This review synthesizes current findings on mitomiRs, their mitochondrial targets, and functions, while also exploring their involvement in cellular aging. Our goal is to shed light on the potential molecular mechanisms by which mitomiRs contribute to the aging process.